2009
DOI: 10.1037/a0015433
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulatory failure and intimate partner violence perpetration.

Abstract: Five studies tested the hypothesis that self-regulatory failure is an important predictor of intimate partner violence (IPV) perpetration. Study 1 participants were far more likely to experience a violent impulse during conflictual interaction with their romantic partner than they were to enact a violent behavior, suggesting that self-regulatory processes help individuals refrain from perpetrating IPV when they experience a violent impulse. Study 2 participants high in dispositional self-control were less like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
399
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 420 publications
(422 citation statements)
references
References 111 publications
18
399
4
1
Order By: Relevance
“…Participants also completed the Babcock et al (2004) 20-item measure of IPV perpetration inclinations. This scale, which we modified for dating rather than married samples (Finkel, DeWall, Slotter, Oaten, & Foshee, 2009), had participants indicate how likely they would become physically aggressive in response to each of 20 hypothetical provocative partner behaviors (1 ¼ Not at all likely that I would be physically aggressive, 9 ¼ Extremely likely that I would be physically aggressive; a ¼ .96). Samples items were, "My partner ridicules or makes fun of me," "My partner does something to offend or 'disrespect' me," and "I find out that my partner has been flirting with someone."…”
Section: Methodsmentioning
confidence: 99%
“…Participants also completed the Babcock et al (2004) 20-item measure of IPV perpetration inclinations. This scale, which we modified for dating rather than married samples (Finkel, DeWall, Slotter, Oaten, & Foshee, 2009), had participants indicate how likely they would become physically aggressive in response to each of 20 hypothetical provocative partner behaviors (1 ¼ Not at all likely that I would be physically aggressive, 9 ¼ Extremely likely that I would be physically aggressive; a ¼ .96). Samples items were, "My partner ridicules or makes fun of me," "My partner does something to offend or 'disrespect' me," and "I find out that my partner has been flirting with someone."…”
Section: Methodsmentioning
confidence: 99%
“…Although it seems that most people who experience an urge to perpetrate IPV are able to override this urge most of the time, some may succumb to it when their self-regulation fails (Finkel et al, 2009).…”
Section: Th Eorymentioning
confidence: 99%
“…Furthermore, a study found that ego depletion resulted in increased aggressive responding after being provoked with insults (DeWall et al 2007). In addition, Finkel et al (2009) found that within a sample of intimate partners, ego-depleted participants were more violent in response to partner provocations than non-depleted participants. It is notable that this study also found that those whose self-regulatory resources were experimentally bolstered in a 2-week training program exhibited less inclinations to violence than those participants whose selfregulatory resources had not been boosted.…”
Section: Self-control and Ego Depletionmentioning
confidence: 99%
“…Despite such a capacity for self-regulation, there are numerous examples in everyday life in which self-control fails. Risky sexual behavior, overeating, drug and alcohol abuse, and aggression can exemplify consequences of a failure to regulate behavior (Baumeister et al 1993;Denson et al 2012;DeWall et al 2011;Finkel et al 2009;Quinn and Fromme 2010;Slotter et al 2012;Stinson et al 2008).…”
Section: Self-control and Ego Depletionmentioning
confidence: 99%